Deployment of multiservice code in FSO-based hybrid subcarrier system - Alnassar, Ghusoon; Mohammed, Husam Abduldaem; Taiwo, Ambali; Ahmad Anas, Siti Barirah; Mokhtar, Makhfudzah (Walter de Gruyter GmbH, 2022)
This research aims to investigate and improve multi-user free space optic systems (FSO) based on a hybrid subcarrier multiplexing spectral amplitude coding-optical code division multiple access (SCM-SAC-OCDMA) technique using MS code with a direct decoding technique. The performance is observed under different weather conditions including clear, rain, and haze conditions. The investigation includes analyzing the proposed system mathematically using MATLAB and OptiSystem software. The simulation is carried out using a laser diode. Furthermore, the performances of the MS code in terms of angles of bit rate, beam divergence and noise are evaluated based on bit error rate (BER), received power, and transmission distance. The performance of the MS code-based system was subsequently compared with Khazani Syed code (KS), multi-diagonal (MD), and modified quadratic congruence code (MQC) codes under different weather conditions at a bit rate of 1 Gb/s and BER threshold of 10−9. Heavy rain indicates the worst performance in terms of transmission distance of 0.9 km. Nevertheless, the system designed using the MS code outperformed the KS, MD and MQC systems as it is capable of supporting up to 6.3, 0.8, 0.9, and 1.5 km, respectively, under clear weather. In conclusion, this study provides a means of improving FSO communications that suits tropical and Malaysia weather conditions.